2017
DOI: 10.1038/s41598-017-12900-8
|View full text |Cite
|
Sign up to set email alerts
|

Selective Homogeneous Assay for Circulating Endopeptidase Fibroblast Activation Protein (FAP)

Abstract: Fibroblast Activation Protein (FAP) is a membrane-bound serine protease whose expression is often elevated in activated fibroblasts associated with tissue remodeling in various common diseases such as cancer, arthritis and fibrosis. Like the closely related dipeptidyl peptidase DPPIV, the extracellular domain of FAP can be released into circulation as a functional enzyme, and limited studies suggest that the circulating level of FAP correlates with the degree of tissue fibrosis. Here we describe a novel homoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 52 publications
1
31
0
Order By: Relevance
“…In vitro specificity studies revealed that KYP‐2047 was a potent and selective inhibitor of POP, and currently, it is widely used in in vitro and in vivo studies. (Bainbridge et al, ; Myöhänen, Hannula, et al, ; Svarcbahs, Julku, & Myohanen, ). We found that POP overexpression increased progesterone production in primary luteal cells (Figure d).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro specificity studies revealed that KYP‐2047 was a potent and selective inhibitor of POP, and currently, it is widely used in in vitro and in vivo studies. (Bainbridge et al, ; Myöhänen, Hannula, et al, ; Svarcbahs, Julku, & Myohanen, ). We found that POP overexpression increased progesterone production in primary luteal cells (Figure d).…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine the levels of soluble FAP, the sFAPDuoSet ELISA kit (R&D Systems, DY3715) was used [ 46 , 47 ]. 100 μl of standards, reagent blank and plasma samples (1/100 dilution) were plated into a 96-well plate and incubated overnight at 4ºC.…”
Section: Methodsmentioning
confidence: 99%
“…More sophisticated delivery methods designed to increase bioavailability to tumors include loading chemotherapeutics into nanoparticle carriers; in this case FAP can be used to activate the drugs( 130 ) or to help dissemble the carrier to mediate drug release and/or uptake( 131 , 132 ). Similar concepts can be applied to imaging techniques for cancer detection by using FAP-cleavable reporter constructs( 133 , 134 ).…”
Section: Fap-targeted Therapiesmentioning
confidence: 99%